Added value of a balloon-based mucosal exposure device in computer-aided detection-assisted colonoscopy: a randomized controlled trial (COMBAT study) - Rocchetto, Simone; Rondonotti, Emanuele; Alicante, Saverio; Buda, Andrea; Segatta, Francesco; Paggi, Silvia; Bina, Nicolò; Di Paolo, Dhanai; Scardino, Giulia; Terreni, Natalia; Mandelli, Giovanna; Andrealli, Alida; et al. (Endoscopy, 2025)
Both computer-aided detection (CADe) systems and mucosal exposure devices can enhance adenoma detection during colonoscopy. This research investigates whether combining a CADe system with a balloon-based mucosal exposure device increases the identification of individuals with high risk colonoscopy findings within a fecal immunochemical test (FIT)-based organized screening program.We conducted a multicenter, open-label, parallel-arm randomized controlled trial. FIT-positive subjects were randomized 1:1 to either CADe-assisted colonoscopy with a balloon-based mucosal exposure device (CADe+balloon arm) or CADe-assisted colonoscopy alone (CADe arm). Randomization was performed using a computer-generated block sequence, with age and sex stratified. Participants, but not endoscopists, were masked to the random assignment. The primary end point was the rate of individuals with high risk colonoscopy findings according to ESGE criteria (≥5 low risk adenomas or ≥1 advanced adenoma or ≥1 advanced serrated lesion). The key secondary end point was the adenoma detection rate (ADR).644 subjects (51.5% women) were randomized in three centers. High risk findings were observed in 19.3% (95%CI 15.0% to 23.5%) of the CADe+balloon arm and 23.1% (95%CI 18.4% to 27.8%) of the CADe arm ( = 0.24). The ADR was 55.4% (95%CI 50.1% to 60.8%) versus 59.1% (95%CI 53.8% to 64.8%) in the CADe+balloon and CADe arms, respectively ( = 0.32). No adverse events were reported.In a FIT-based screening program, adding a balloon-based mucosal exposure device to CADe-assisted colonoscopy did not enhance the detection of subjects with high risk features or of neoplastic lesions. A CADe-related ceiling effect may have limited the benefit of the additional device.